Effectiveness of intercostal nerves in restoration of elbow flexion in devastating brachial plexus injuries - Bhandari, PS; Sadhotra, LP; Bhargava, P; Bath, AS; Mukherjee, MK; Bhatti, TS; Maurya, S (Indian Journal of Neurotrauma, 2009)
In extensive lesions with root avulsions, intercostal nerves provide the source of motor axons to reanimate the elbow flexors. In long standing cases, nerve transfers are no longer effective. These patients can be rehabilitated with free functioning muscle transfers innervated by the intercostals nerves. Between September 2003 and February 2006, 48 patients with devastating brachial plexus injuries underwent intercostal nerve transfers. In 22 patients with complete palsy (C5 to T1) three intercostal nerves (3rd,4th & 5th) were directly sutured to the musculocutaneous nerve. Sixteen patients had C5, C6 and C7 injuries. In 12 of these patients all the three roots were avulsed. In the remaining four, C7 spinal nerve was adhered to the scar tissue and was treated by microneurolysis. In all patients three intercostal nerves were directly coapted with the musculocutaneous nerve. Ten patients, presenting one or more years after the injury underwent free functioning muscle transfer using gracilis muscle motored by two or three intercostal nerves. Results of nerve transfers were better in the partial injury group (16 patients) with 7 patients regaining MRC grade 4, and 5 patients MRC grade 3. Four patients could achieve only M2 grade. In the total group (22 patients) only four could restore MRC grade 4 function. Eight patients attained MRC grade 3 and four patients MRC grade 2. Six patients could not restore elbow flexion. In the late group (10 patients) free functioning muscle transfer restored MRC grade 4 elbow flexion in 1 patient and MRC grade 3 function in another 5 patients. In the remaining 4 patients muscle transfer was not successful. We conclude that direct coaptation of intercostal nerves to the musculocutaneous nerve is a viable option to restore elbow flexion in total plexus injuries. Intercostal nerves are also suitable motor donors for free functioning muscle transfers.
Keywords: brachial plexus injury; elbow flexion; intercostal nerve transfer